Pacing Strategies in the ‘Athens Classic Marathon’: Physiological and Psychological Aspects - Nikolaidis, Pantelis T.; Knechtle, Beat (Frontiers in Physiology, 2018)
Despite the increased scientific interest in the relationship between pacing and performance in marathon running, little information is available about the association of pacing with physiological and psychological parameters. Therefore, the aim of the present study was to examine the role physical fitness and training characteristics on pacing in the ‘Athens Classic Marathon’. Finishers in this race in 2017 (women, n=26, age 40.8±9.4 years; men, n=130, age 44.1±8.6 years) were analyzed for their pacing during the race, completed the Motivation of Marathon Scale (MOMS) and performed a series of physiological tests. Women and faster recreational runners adopted a more even pacing. A more even pacing was related with a higher aerobic capacity and lower muscle strength in men, but not in women. Men with more even pacing scored higher in psychological coping, self-esteem, life meaning, recognition and competition than their counterparts with less even pacing. Considering the increasing number of participants in marathon races, these findings might help a wide range of professionals (fitness trainers, physiologists, psychologists) working with runners to optimize the pacing of their athletes.